Analisis Pemerolehan Bahasa Terhadap Perkembangan Bahasa Anak Usia 8 Tahun - Prastiwi, Maulia Widya; Wahyu Ningsih, Sulis; Raskian Aji, Dimas; Kholifatul, Ratna; Fauziah, Muhardila (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to find out about children's language acquisition towards children's language development at the age of 8 years. The purpose of this study is to analyze children's language acquisition at the age of 8 years who experience a phase of speech delay on their language development.  Researchers use qualitative research, and this type of research natural observation method involves observing and recording certain behaviors, situations, or events, without direct interaction with the subject. The approach used in this research is a qualitative approach with natural observation methods. Acquisition techniques methods in this observation used 3 ways, namely interview techniques, experiments, and observations. Based on the results of data analysis, children’s language skills are influenced by the first language obtained and environmental factors that children live in. Another factor that affects children's language acquisition is the child's fluency factor, this is the cause of delayed language acquisition in children. Based on the results of the study, language development in children is influenced by the child's language acquisition process. The role of parents is quite important in this aspect of children's language development.